(untitled) (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the university type of the system of higher education in Switzerland. Peculiarity of management of Swiss higher school is analysed, different components of this structure are defined. The emphasis is put on the principie of close cooperation between the Confederation and the cantons as well as the distribution of powers.